Uranium oxide composite fuel pellet and preparation method thereof
By forming a composite structural layer on the outer surface of the UN core pellet, the problems of low thermal conductivity of UO2 fuel pellets and corrosion oxidation of uranium nitride fuel are solved, and the high thermal conductivity and corrosion resistance of the fuel pellets are improved.
Patent Information
- Application Number
- CN202411715994.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
The thermal conductivity of existing UO2 fuel pellets is low, which leads to a high central temperature of the pellet during the reactor operation, storing a large amount of heat, increasing the risk of accidents; while uranium nitride fuel has a high thermal conductivity, but is not resistant to high-temperature water corrosion.
A uranium oxide composite fuel pellet is provided, including a UN core pellet and a composite structural layer composited on the outer surface of the UN core pellet. The composite structural layer consists of a metal transition layer, an anti-corrosion oxide layer and a metal protective layer. Through these layers, the thermal conductivity and corrosion resistance of the fuel pellet are improved.
It improves the thermal conductivity and resistance to high-temperature water vapor corrosion of fuel core pellets, reduces the risk in accidents, and solves the corrosion and oxidation problem of uranium nitride fuel in light water reactors.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nuclear fuel, and in particular to a uranium oxide composite fuel pellet and a preparation method thereof. Background Art
[0002] At present, the main type of nuclear power plant in the world is light water reactor, and most of them use UO2 pellets as fuel; UO2 pellets have the advantages of mature manufacturing process, high melting point, high chemical and irradiation stability. However, the thermal conductivity of UO2 is low, only about 3.5W·m at 800℃. -1 ·K -1 , and the thermal conductivity decreases with increasing temperature. Therefore, the UO2 fuel pellets have poor heat dissipation capacity. When the reactor is running, the center temperature of the pellets is very high, and a large amount of heat will be stored in the fuel pellets. Under accident conditions, the heat stored in the fuel pellets and the decay heat of the fission products will rapidly increase the temperature of the zirconium alloy cladding, and then the zirconium alloy will rapidly undergo an exothermic oxidation reaction with water vapor to produce a large amount of heat and hydrogen, accelerating the meltdown of the core and possibly causing a hydrogen explosion. Therefore, improving the thermal conductivity of the fuel pellets and strengthening their heat dissipation capacity is one of the important means to improve the safety of nuclear fuel.
[0003] The uranium metal density of uranium nitride (UN) fuel is 13.5 gU / cm 3 , higher than UO2's 9.7gU / cm 3 , the thermal conductivity is also 20W·m- 1 ·K -1 The thermal conductivity increases with the increase of temperature. However, compared with UO2 fuel, uranium nitride fuel also has the disadvantages of high chemical activity and poor resistance to high temperature water corrosion. Therefore, solving the corrosion and oxidation of uranium nitride fuel in light water reactors is the most important problem that must be solved to replace the existing UO2 fuel. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a uranium oxide composite fuel pellet and a preparation method thereof.
[0005] The technical solution adopted by the present invention to solve the technical problem is: to provide a uranium oxide composite fuel pellet, including a UN pellet and a composite structural layer composited on the outer surface of the UN pellet; the composite structural layer includes a metal transition layer, an anti-corrosion oxidation layer and a metal protective layer composited in sequence from the inside to the outside;
[0006] The metal transition layer is formed of a high melting point metal, and its thermal expansion coefficient is close to that of the UN core block; the metal protective layer can react with high temperature steam during oxidation to form a dense anti-oxidation film.
[0007] In some embodiments, the metal transition layer is formed of one or more of Ti, Cr, TiN, CrN, and VN.
[0008] In some embodiments, the metal protection layer is formed of metal Cr.
[0009] In some embodiments, the corrosion resistant oxide layer is formed by one or more of ZrB2, TiB2, SiC, CrTiZrB, and CrTiZrN.
[0010] In some embodiments, when the corrosion-resistant oxide layer is a CrTiZrB layer or a CrTiZrN layer, it can generate a dense Cr2O3, TiO2, or ZrO2 oxide layer during the oxidation process.
[0011] In some embodiments, when the corrosion-resistant oxide layer is a CrTiZrB layer, the atomic content of Cr element in CrTiZrB is 45±1%, the atomic content of Ti element is 30±1%, the atomic content of Zr element is 23±1%, and the atomic content of B element is 2±1%.
[0012] In some embodiments, when the corrosion-resistant oxide layer is a CrTiZrN layer, the atomic content of Cr element in CrTiZrN is 40±1%, the atomic content of Ti element is 30±1%, the atomic content of Zr element is 25±1%, and the atomic content of B element is 5±1%.
[0013] In some embodiments, the thickness of the metal transition layer is ≤10 μm; the thickness of the anti-corrosion oxide layer is 20 μm to 50 μm; and the thickness of the metal protective layer is 3 μm to 7 μm.
[0014] The present invention also provides a method for preparing a uranium oxide composite fuel pellet, comprising the following steps:
[0015] S1. Prepare UN pellets;
[0016] S2, preparing a metal transition layer on the surface of the UN core block;
[0017] S3, preparing an anti-corrosion oxide layer outside the metal transition layer;
[0018] S4, preparing a metal protective layer on the anti-corrosion oxide layer.
[0019] In some embodiments, the metal transition layer, the anti-corrosion oxide layer and the metal protective layer are respectively formed by at least one of magnetron sputtering, multi-arc ion plating, physical vapor deposition and chemical vapor deposition.
[0020] In some embodiments, in step S1, UN core block raw material powder is selected and prepared by hot pressing sintering or spark plasma sintering; when hot pressing sintering is selected, the atmosphere is vacuum, the temperature is 1350℃~1700℃, and the sintering pressure is 50Mpa~100Mpa; when spark plasma sintering is selected, the atmosphere is inert atmosphere, the sintering temperature is 1000℃~1900℃, and the pressure is 30Mpa~150Mpa.
[0021] The beneficial effects of the present invention are as follows: by arranging a composite structural layer outside the UN core block, the high-temperature water corrosion resistance of the fuel core block is improved, wherein the composite bonding layer is bonded to the core block through a metal transition layer with thermal expansion matching, thereby avoiding the risk of the composite structural layer falling off under high-temperature thermal stress due to insufficient bonding force; and solving the problem of ATF fuel being applied to pressurized water reactors. DETAILED DESCRIPTION
[0022] The uranium oxide composite fuel pellet of the present invention comprises a UN pellet and a composite structural layer composited on the outer surface of the UN pellet; the composite structural layer has a three-layer structure, specifically comprising a metal transition layer, an anti-corrosion oxidation layer and a metal protective layer composited in sequence from the inside to the outside.
[0023] The metal transition layer is the innermost layer, in contact with the UN pellet, and as an intermediate transition layer between the UN pellet and the anti-corrosion oxide layer, it can effectively improve the bonding force between the anti-corrosion oxide layer and the fuel pellet matrix, and prevent it from falling off due to stress at high temperature. The metal transition layer is formed of a high melting point metal, and its thermal expansion coefficient is close to that of the UN pellet, preferably formed of one or more of Ti, Cr, TiN, CrN, and VN, and can be formed on the outer surface of the UN pellet by at least one of magnetron sputtering, multi-arc ion plating, physical vapor deposition, plasma enhanced chemical vapor deposition (PECVD), and chemical vapor deposition.
[0024] The anti-corrosion oxide layer is used as a working layer and can be firmly bonded to the outer surface of the UN pellet through the inner metal transition layer. The anti-corrosion oxide layer can react with high-temperature steam during the oxidation process to form a dense oxide layer, thereby improving the high-temperature steam corrosion resistance of the fuel pellet.
[0025] The corrosion-resistant oxide layer is formed by one or more of ZrB2, TiB2, SiC, CrTiZrB, and CrTiZrN.
[0026] When the anti-corrosion oxide layer is a CrTiZrB layer or a CrTiZrN layer, it can generate dense Cr2O3, TiO2, and ZrO2 oxide layers during the oxidation process. When the anti-corrosion oxide layer is a CrTiZrB layer, the atomic content of Cr element in CrTiZrB is 45±1%, the atomic content of Ti element is 30±1%, the atomic content of Zr element is 23±1%, and the atomic content of B element is 2±1%. When the anti-corrosion oxide layer is a CrTiZrN layer, the atomic content of Cr element in CrTiZrN is 40±1%, the atomic content of Ti element is 30±1%, the atomic content of Zr element is 25±1%, and the atomic content of B element is 5±1%.
[0027] In the anti-corrosion oxide layer, such as the CrTiZrB layer, the Cr, Ti, and Zr elements are oxidized to form a protective oxide film, which can effectively prevent the anti-corrosion oxide layer from being corroded in high-temperature and high-pressure water. The target material used in the anti-corrosion oxide layer is relatively low in price, which can effectively reduce costs.
[0028] As the outermost layer, the metal protective layer can react with high-temperature steam during the oxidation process to form a dense anti-oxidation film. The metal protective layer is preferably formed of metal Cr, which can form a dense Cr2O3 film during the oxidation process, which can effectively prevent oxygen from diffusing into the matrix, protect the matrix from corrosion, and solve the problem of ATF fuel being used in pressurized water reactors.
[0029] The thickness of the composite structure layer is:
[0030] The thickness of the metal transition layer is ≤10 μm, preferably 4 μm to 8 μm. If the metal transition layer is too thin, sufficient interface bonding cannot be formed, resulting in insufficient adhesion; if the metal transition layer is too thick, excessive stress will accumulate inside the metal transition layer, resulting in cracking or peeling of the metal transition layer.
[0031] The thickness of the corrosion-resistant oxide layer is 20 μm to 50 μm, preferably 25 μm to 35 μm.
[0032] The thickness of the metal protective layer is 3 μm to 7 μm, preferably 4 μm to 6 μm. The product Cr2O3 after the metal protective layer is oxidized with water vapor has high density and can effectively protect the fuel pellet matrix from being oxidized.
[0033] The method for preparing the uranium oxide composite fuel pellets of the present invention may include the following steps in one embodiment:
[0034] S1. Prepare UN pellets.
[0035] The UN pellet raw material powder is selected and prepared by hot pressing sintering or spark plasma sintering (SPS).
[0036] When hot pressing sintering is selected, the atmosphere is vacuum, the temperature is 1350℃~1700℃, and the sintering pressure is 50Mpa~100Mpa; when SPS sintering is selected, the atmosphere is inert atmosphere, the sintering temperature is 1000℃~1900℃, and the pressure is 30Mpa~150Mpa.
[0037] S2, preparing a metal transition layer on the surface of the UN core block;
[0038] When the metal transition layer is prepared by magnetron sputtering, pure metal raw materials are used as target materials.
[0039] When the metal transition layer is prepared by metal nitride, physical vapor deposition (PVD) can be used: high-energy particles (such as argon ions) are used to bombard the titanium target material, so that titanium atoms are sputtered out and react with the reaction gas (such as nitrogen) to form a TiN layer. Chemical vapor deposition or plasma enhanced chemical vapor deposition (PECVD) can also be used. In the preparation method, the physical vapor deposition process is preferred, and the formed technical transition layer has a higher degree of bonding with the substrate.
[0040] S3. Prepare a corrosion-resistant oxide layer outside the metal transition layer.
[0041] Preferably, the corrosion-resistant oxide layer is deposited outside the metal transition layer by magnetron sputtering.
[0042] S4. Prepare a metal protective layer on the corrosion-resistant oxide layer.
[0043] Preferably, magnetron sputtering is used to deposit the metal protection layer outside the corrosion-resistant oxide layer.
[0044] In a specific embodiment, the composite layer is deposited on the surface of the fuel pellet (UN pellet) by magnetron sputtering technology, and the purity of the Ar gas and N2 gas used is 99.9999 vol.%. The specific preparation process includes the following steps:
[0045] (1) Surface ion etching of UN core blocks
[0046] The sintered UN core block was placed on the sample stage in the vacuum chamber of the magnetron sputtering equipment, and the vacuum degree in the vacuum chamber was pumped to 9×10 -5 Pa, and then Ar gas is introduced to keep the pressure in the vacuum chamber at 0.1 Pa, and the gas flow rate is maintained at 400 sccm. During the ion etching process of the material surface, the cathode is a metal Cr target, the current is 150 A, the temperature is 500 ° C, and the etching time is 60 min.
[0047] The surface of the UN core block is ion-etched to facilitate the subsequent deposition of the composite structure layer and improve the adhesion stability of the composite structure layer.
[0048] (2) Deposition of the innermost layer of Ti / Cr / TiN / CrN / VN on the UN core block after ion etching
[0049] Ar gas was continued to be used as the working gas, the pressure was maintained at 0.1Pa-0.5Pa, the gas flow rate was maintained at 500sccm, the current was 60A-120A, the temperature was 450℃-500℃, and the spraying time was 30min-40min during the deposition of the metal transition layer.
[0050] (3) Depositing a ZrB2 / TiB2 / SiC / CrTiZrB layer on the surface of the metal transition layer obtained in step (2)
[0051] After the metal transition layer is deposited, stop introducing Ar gas and then introduce N2 (nitrogen gas). N2 is used as the working gas, the N2 pressure is adjusted to 1Pa~2Pa, the gas flow rate is 1200sccm, the current during the deposition process is 80A~120A, the temperature is 400℃~450℃, and the spraying time is 180min~230min.
[0052] (4) depositing a metal Cr protective layer on the surface of the anti-corrosion oxide layer deposited in step (3).
[0053] After the CrTiZrB layer is deposited, the N2 flow is stopped and Ar gas is used as the working gas. The pressure is maintained at 0.1Pa~0.5Pa, the gas flow rate is maintained at 450sccm, the current during the deposition process is 60A~120A, the temperature is 400℃~450℃, and the spraying time is 30min~40min.
[0054] In the present invention, a composite layer is deposited on the surface of a fuel pellet (UN pellet) by using magnetron sputtering technology. The magnetron sputtering technology has many advantages: high deposition rate, small substrate temperature rise, and small damage to the film layer; the thin film obtained by sputtering has good bonding with the substrate; the thin film obtained by sputtering has high purity, good density, and good film uniformity; the sputtering process has good repeatability, and a thin film with uniform thickness can be obtained on a large-area substrate; the thickness of the layer can be accurately controlled, and the size of the particles constituting the thin film can be controlled by changing parameter conditions; and it is easy to realize industrialization.
[0055] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A uranium oxide composite fuel pellet, characterized in that: It comprises a UN core block and a composite structure layer composited on the outer surface of the UN core block; the composite structure layer comprises a metal transition layer, an anti-corrosion oxidation layer and a metal protective layer composited in sequence from inside to outside; The metal transition layer is formed of a high melting point metal, and its thermal expansion coefficient is close to that of the UN core block; the metal protective layer can react with high temperature steam during oxidation to form a dense anti-oxidation film.
2. The uranium oxide composite fuel pellet according to claim 1, characterized in that: The metal transition layer is formed of one or more of Ti, Cr, TiN, CrN and VN.
3. The uranium oxide composite fuel pellet according to claim 1, characterized in that: The metal protection layer is formed of metal Cr.
4. The uranium oxide composite fuel pellet according to claim 1, characterized in that: The corrosion-resistant oxide layer is formed by one or more of ZrB2, TiB2, SiC, CrTiZrB, and CrTiZrN.
5. The uranium oxide composite fuel pellet according to claim 4, characterized in that: When the corrosion-resistant oxide layer is a CrTiZrB layer or a CrTiZrN layer, it can generate a dense Cr2O3, TiO2, ZrO2 oxide layer during the oxidation process.
6. The uranium oxide composite fuel pellet according to claim 4, characterized in that: When the anti-corrosion oxide layer is a CrTiZrB layer, the atomic content of Cr element in CrTiZrB is 45±1%, the atomic content of Ti element is 30±1%, the atomic content of Zr element is 23±1%, and the atomic content of B element is 2±1%; When the anti-corrosion oxidation layer is a CrTiZrN layer, the atomic content of Cr element in CrTiZrN is 40±1%, the atomic content of Ti element is 30±1%, the atomic content of Zr element is 25±1%, and the atomic content of B element is 5±1%.
7. The uranium oxide composite fuel pellet according to any one of claims 1 to 6, characterized in that: The thickness of the metal transition layer is ≤10 μm; the thickness of the anti-corrosion oxidation layer is 20 μm to 50 μm; and the thickness of the metal protective layer is 3 μm to 7 μm.
8. A method for preparing a uranium oxide composite fuel pellet according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Prepare UN pellets; S2, preparing a metal transition layer on the surface of the UN core block; S3, preparing an anti-corrosion oxide layer outside the metal transition layer; S4, preparing a metal protective layer on the anti-corrosion oxide layer.
9. The method for preparing uranium oxide composite fuel pellets according to claim 8, characterized in that: The metal transition layer, the anti-corrosion oxidation layer and the metal protection layer are respectively formed by at least one of magnetron sputtering, multi-arc ion plating, physical vapor deposition and chemical vapor deposition.
10. The method for preparing uranium oxide composite fuel pellets according to claim 8 or 9, characterized in that: In step S1, UN pellet raw material powder is selected and prepared by hot pressing sintering or spark plasma sintering; When hot pressing sintering is selected, the atmosphere is vacuum, the temperature is 1350°C ~ 1700°C, and the sintering pressure is 50Mpa ~ 100Mpa; when spark plasma sintering is selected, the atmosphere is inert atmosphere, the sintering temperature is 1000°C ~ 1900°C, and the pressure is 30Mpa ~ 150Mpa.
Citation Information
Patent Citations
High-temperature oxidation resistant coating for cladding substrate and preparation process
CN113293354A
High-uranium-density nuclear fuel pellet with anticorrosive coating and preparation method of high-uranium-density nuclear fuel pellet
CN115910392A
Metal alloy cladding rod-shaped fuel element based on foam metal
CN116504428A
High uranium density ATF nuclear fuel pellet and preparation method thereof
CN116711026A
Coaxial composite fuel pellet and preparation method thereof
CN117238537A